2013
DOI: 10.1098/rsif.2013.0298
|View full text |Cite
|
Sign up to set email alerts
|

Modelling seasonal influenza: the role of weather and punctuated antigenic drift

Abstract: Seasonal influenza appears as annual oscillations in temperate regions of the world, yet little is known as to what drives these annual outbreaks and what factors are responsible for their inter-annual variability. Recent studies suggest that weather variables, such as absolute humidity, are the key drivers of annual influenza outbreaks. The rapid, punctuated, antigenic evolution of the influenza virus is another major factor. We present a new framework for modelling seasonal influenza based on a discrete-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 44 publications
(59 reference statements)
5
49
2
2
Order By: Relevance
“…For the United States, absolute humidity was identified as a critical determinant of 24 observed influenza mortality (Barreca and Shimshack, 2012) and anomalously low humidity levels were found to precede the onset of increased wintertime influenza-related mortality in the United States by several weeks (Davis et al, 2012;Shaman et al, 2010). The respiratory impact of low atmospheric humidity was evident in other studies in Belgium (Lander et al, 2012), China (Xiao et al, 2013), Japan (Harata et al, 2004), Israel (Yaari et al, 2010), the Netherlands and Portugal (van Noort et al, 2012), and was inferred in forensic studies of major historical influenza outbreaks in England and Wales (He et al, 2013). Yet in studies that utilized relative humidity, Zhang et al (2013) found a negative association between RSV and Rodriguez-Martinez (2015) uncovered no relationship.…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 67%
“…For the United States, absolute humidity was identified as a critical determinant of 24 observed influenza mortality (Barreca and Shimshack, 2012) and anomalously low humidity levels were found to precede the onset of increased wintertime influenza-related mortality in the United States by several weeks (Davis et al, 2012;Shaman et al, 2010). The respiratory impact of low atmospheric humidity was evident in other studies in Belgium (Lander et al, 2012), China (Xiao et al, 2013), Japan (Harata et al, 2004), Israel (Yaari et al, 2010), the Netherlands and Portugal (van Noort et al, 2012), and was inferred in forensic studies of major historical influenza outbreaks in England and Wales (He et al, 2013). Yet in studies that utilized relative humidity, Zhang et al (2013) found a negative association between RSV and Rodriguez-Martinez (2015) uncovered no relationship.…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 67%
“…In a previous work, we have focused on modelling the stochasticity of the infection process described by the transmission model and the stochasticity in the reporting of clinical diagnoses [8]. Here, for the sake of simplicity, the stochasticities involved in these processes are ignored, and the likelihood function is based on the stochasticity of the sampling processes involved in the laboratory testing, as it is assumed that the latter are dominant, owing to the small populations involved in these data.…”
Section: Inferencementioning
confidence: 99%
“…Figure 6b rsif.royalsocietypublishing.org J. R. Soc. Interface 13: 20160099 population as a whole, the optimal allocation strategy, which reduces the total attack rate to a minimum, is to vaccinate almost only school children (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Vaccinating just 15% of the population using the optimal allocation strategy (vaccinating 58% of all school children) would have completely mitigated the winter wave of the outbreak.…”
Section: Effect Of Optimal Vaccine Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the circumstances, influenza typically infects between 10% and 50% of a given population and has become a source of considerable human morbidity and mortality (2). There is much controversy in identifying the seasonal drivers that generate annual influenza epidemics and the processes that give rise to their large variability (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This is an outstanding problem of influenza research today.…”
mentioning
confidence: 99%